Learning Polyhedrons Based On It - Hajar, Siti (MEJ (Mathematics Education Journal), 2018)
Learning resources and media play very important roles in learningactivities in the classroom. Various learning resources complemented withinteractional media will encourage the learners to be more active in theclassroom. The objective of this present research is to analyze whatlearning resources and media are used by the teacher in learningpolyhedrons. This research was conducted in MTs N Malang 1. Themethods of data collection were observations and interviews. To obtain thedata, the researcher made observations during learning activities and thencompared the data from the observations and those of the interviews withthe teacher concerned and with one of the students joining in the learningactivities. The data were qualitative in nature. Based on the data analysis, itwas revealed that learning resources and media used were IT-based. Thelearning resources were electronic books and the package books for GradeVIII and the media were the property from Power Point. The learningbasedIT for students Grade VIII-A MTs N Malang 1 gave good effects on allstudents, so that all of them joined in the learning activities actively.